New Antituberculosis Drugs: From Clinical Trial to Programmatic Use - Gualano, Gina; CAPONE, Susanna; MATTEELLI, Alberto; Palmieri, Fabrizio (Infectious Disease Reports, 2016)
Treatment of multidrug-resistant tuberculosis (MDR-TB) cases is challenging because it relies on second-line drugs that are less potent and more toxic than those used in the clinical management of drug-susceptible TB. Moreover, treatment outcomes for MDR-TB are generally poor compared to drug sensitive disease, highlighting the need for of new drugs. For the first time in more than 50 years, two new anti-TB drugs were approved and released. Bedaquiline is a first-in-class diarylquinoline compound that showed durable culture conversion at 24 weeks in phase IIb trials. Delamanid is the first drug of the nitroimidazole class to enter clinical practice. Similarly to bedaquiline results of phase IIb studies showed increased sputum-culture conversion at 2 months and better final treatment outcomes in patients with MDR-TB. Among repurposed drugs linezolid and carbapenems may represent a valuable drug to treat cases of MDR and extensively drugresistant TB. The recommended regimen for MDR-TB is the combination of at least four drugs to which M. tuberculosis is likely to be susceptible for the duration of 20 months. Drugs are chosen with a stepwise selection process through five groups on the basis of efficacy, safety, and cost. Clinical phase III trials on new regimen are ongoing that could prove transformative against MDR-TB, by being shorter (six months), simpler (an alloral regimen) and safer than current standard therapy. It is fundamental that the adoption of the new drugs is done responsibly to avoid inappropriate use. Concentration of inpatient MDR-TB treatment in specialized centers could be considered in countries with low numbers of cases in order to provide appropriate clinical case management and to prevent emergence of drug resistance.